Antibiotic Susceptibilities of Salmonella enterica Serovar Typhi and S. enterica Serovar Paratyphi A Isolated from Patients in Japan - Hirose, Kenji (American Society for Microbiology, 2001)
The antibiotic susceptibilities of 62 strains of Salmonella enterica serovar Typhi and 37 strains of S. enterica serovar Paratyphi A were investigated with 18 antibiotics. Eighteen S. enterica serovar Typhi isolates and five S. enterica serovar Paratyphi A isolates were resistant to one or more antimicrobial agents, among which 10 S. enterica serovar Typhi isolates were nalidixic acid resistant and also showed decreased ciprofloxacin susceptibility.